2018
DOI: 10.5194/tc-12-1211-2018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year analysis of distributed glacier mass balance modelling and equilibrium line altitude on King George Island, Antarctic Peninsula

Abstract: Abstract. The South Shetland Islands are located at the northern tip of the Antarctic Peninsula (AP). This region was subject to strong warming trends in the atmospheric surface layer. Surface air temperature increased about 3 K in 50 years, concurrent with retreating glacier fronts, an increase in melt areas, ice surface lowering and rapid break-up and disintegration of ice shelves. The positive trend in surface air temperature has currently come to a halt. Observed surface air temperature lapse rates show a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 79 publications
2
56
0
Order By: Relevance
“…The dEBM and two empirical schemes are calibrated and evaluated using the state-of-the-art regional climate and snowpack model MAR (Fettweis et al, 2017) as a reference.…”
Section: Derivation Of T and Qmentioning
confidence: 99%
See 1 more Smart Citation
“…The dEBM and two empirical schemes are calibrated and evaluated using the state-of-the-art regional climate and snowpack model MAR (Fettweis et al, 2017) as a reference.…”
Section: Derivation Of T and Qmentioning
confidence: 99%
“…This new scheme only requires monthly means of temperature and solar radiation as input but implicitly resolves the diurnal cycle of radiation. In a first application on the Greenland Ice Sheet (GrIS) we use a simulation of Greenland's climate of the years 1948 to 2016 with the stateof-the-art regional climate and snowpack model MAR (version 3.5.2 forced with reanalysis data from the National Centers for Environmental Prediction-National Center for Atmospheric Research (NCEP) for the years 1948-2016, Kalnay et al, 1996;Fettweis et al, 2017) as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…The total area of the island is 1250 km 2 , and almost the entire island is covered by ice caps (Figure 2b). The glacier drains the Warszawa Ice field at its Eastern edge (Figure 2c), where melt The reactions of glaciers, generally in the form of mass loss [18], glacier recession [13], and decreased ice surface elevation [16], have been observed, especially for those located in the South Shetland Islands [18][19][20][21][22][23]. Since 1956, climate warming has been the main factor causing these changes.…”
Section: Study Sitementioning
confidence: 99%
“…For example, Simoes et al [26] based on the analysis of the transient snow line positioning obtained from remote sensing data claimed that the ELA for the King George Island Ice Cape equaled 300-350 m but Braun et al [55] based on the same method as Simoes et al [26], suggested that for the northern side of KGI it was 250 m. More specifically, Bintanja [56] estimated that for the Ecology Glacier ELA is 100 m. More recent direct observation with the use of stakes done by Sobota et al [24] for Ecology and Sphinx Glacial System (ESGS) suggested that the average ELA in 2012-2013 was 156 m a.s.l. On the other hand, Falk et al [20], based on their own glaciological observation, calculated the average ELA for Fourcad Glacier over the period 2010-2015 and obtained that it was 260 ± 20 m. All of the published studies suggested that since 1980, the ELA for KGI has been rather stable with small negative mass balance [20], but all studies expected further glacial retreat. As the Baranowski Glacier is the closest to ESGS and even being the part of this system, it can be assumed that the ELA of Baranowski Glacier is around 150 m and is presented in Figure 7, this isoline since 1989 rose higher from Siodło and the surface of the glacier started to thin in the following years.…”
Section: Ice Surface Elevation Changesmentioning
confidence: 99%
See 1 more Smart Citation